1999
DOI: 10.1074/jbc.274.4.2193
|View full text |Cite
|
Sign up to set email alerts
|

α1-Syntrophin Gene Disruption Results in the Absence of Neuronal-type Nitric-oxide Synthase at the Sarcolemma but Does Not Induce Muscle Degeneration

Abstract: ␣1-Syntrophin is a member of the family of dystrophin-associated proteins and is strongly expressed in the sarcolemma and the neuromuscular junctions. All three syntrophin isoforms have a PDZ domain that appears to participate in protein-protein interactions at the plasma membrane. ␣1-Syntrophin has additionally been shown to associate with neuronal nitric-oxide synthase (nNOS) through PDZ domains in vitro. These observations suggest that ␣1-syntrophin may work as a modular adaptor protein that can link nNOS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(176 citation statements)
references
References 30 publications
(44 reference statements)
9
166
1
Order By: Relevance
“…It was reported that nNOS is anchored at the subsarcolemma through its binding to the rod domain of dystrophin at the 16 and 17 rod repeats encoded by exons 42-45 and by interaction with α1-syntrophin (20,21). The truncated dystrophin induced by skipping exons 45-55 would lack half of the 17 rod repeat, thus disturbing the site-responsible anchoring of nNOS and possibly rendering its subsarcolemmal localization unstable.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that nNOS is anchored at the subsarcolemma through its binding to the rod domain of dystrophin at the 16 and 17 rod repeats encoded by exons 42-45 and by interaction with α1-syntrophin (20,21). The truncated dystrophin induced by skipping exons 45-55 would lack half of the 17 rod repeat, thus disturbing the site-responsible anchoring of nNOS and possibly rendering its subsarcolemmal localization unstable.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent images were viewed with an AxioCam HRc microscope from Carl Zeiss Vision GmbH (Munich, Germany) and recorded with a digital camera using Axiovision 4 image acquisition software. Haematoxylin and eosin (H&E) staining of tissue sections, labelling of nuclei with DAPI, and histochemical staining for succinate dehydrogenase and NADPH diaphorase were performed by standard procedures (Kameya et al, 1999;Yasuda et al, 2002;Dowling et al, 2004).…”
Section: Immunofluorescence Microscopy and Histochemical Stainingmentioning
confidence: 99%
“…The sarcolemmal nNOSμ association requires α-syntrophin, dystrophin, and α-dystrobrevin (Brenman et al 1995(Brenman et al , 1996Grady et al 2000;Adams et al 2000Adams et al , 2008. In mice, nNOSμ is not only localized at the sarcolemma, but is also normally expressed at relatively high levels in the cytoplasm (Chang et al 1996;Kameya et al 1999;Thomas et al 2003). However, in human muscle approximately 75% of nNOSμ is associated with the sarcolemmal DGC, suggesting species-specific differences in nNOSμ distribution (Chang et al 1996).…”
Section: Introductionmentioning
confidence: 99%